Somatic mutations of thymic epithelial tumors with myasthenia gravis - Pardini, Eleonora; Cucchiara, Federico; Palumbo, Sara; Tarrini, Giulia; Di Vita, Alessia; Coppedè, Fabio; Nicolì, Vanessa; Guida, Melania; Maestri, Michelangelo; Ricciardi, Roberta; Aprile, Vittorio; Ambrogi, Marcello C.; et al. (Frontiers in Oncology, 2023)
Background: Thymic epithelial tumors are rare malignant neoplasms that are frequently associated with paraneoplastic syndromes, especially myasthenia gravis. GTF2I is an oncogene mutated in a subgroup of thymomas that is reputed to drive their growth. However, for GTF2I wild-type tumors, the relevant mutations remain to be identified.We performed a meta-analysis and identified 4,208 mutations in 339 patients. We defined a panel of 63 genes frequently mutated in thymic epithelial tumors, which we used to design a custom assay for next-generation sequencing. We sequenced tumor DNA from 67 thymomas of patients with myasthenia gravis who underwent resection in our institution.Results: Among the 67 thymomas, there were 238 mutations, 83 of which were in coding sequences. There were 14 GTF2I mutations in 6 A, 5 AB, 2 B2 thymomas, and one in a thymoma with unspecified histology. No other oncogenes showed recurrent mutations, while sixteen tumor suppressor genes were predicted to be inactivated. Even with a dedicated assay for the identification of specific somatic mutations in thymic epithelial tumors, only GTF2I mutations were found to be significantly recurrent.Our evaluation provides insights into the mutational landscape of thymic epithelial tumors, identifies recurrent mutations in different histotypes, and describes the design and implementation of a custom panel for targeted resequencing. These findings contribute to a better understanding of the genetic basis of thymic epithelial tumors and may have implications for future research and treatment strategies.